High-strength modified calcium carbonate and preparation method thereof

Through the preparation method of modified calcium carbonate, the porous vaterite phase nano calcium carbonate and organic crosslinking network structure is used to solve the problem of insufficient dispersion and strength of calcium carbonate in organic polymer matrix, and the uniform dispersion and mechanical properties of high-strength modified calcium carbonate in composite materials are achieved.

CN120399477APending Publication Date: 2025-08-01JIANGXI STONE CALCIUM IND CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510572717.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-06
Publication Date
2025-08-01

AI Technical Summary

Technical Problem

Unmodified calcium carbonate has poor dispersion in organic polymer matrix, resulting in agglomeration, affecting the mechanical properties and processing properties of the composite material. At the same time, its own strength is low, making it difficult to effectively bear stress, and reduce the strength and durability of the composite material.

Method used

Based on porous vaterite nano-calcium carbonate, through graft modification and internal crosslinking network structure, the coupling reaction of 3-(isobutylenyloxy)propyltrimethylsiloxane and poly(ethylene glycol) diacrylate is used to form a chemical bonding and organic crosslinking network to improve the compatibility and strength of calcium carbonate with polymers.

Benefits of technology

It improves the dispersion and compatibility of calcium carbonate in polymer matrix, enhances the strength and durability of composite materials, reduces the possibility of agglomeration, provides internal support, and prevents structural damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120399477A_ABST
    Figure CN120399477A_ABST
Patent Text Reader

Abstract

The invention provides high-strength modified calcium carbonate and a preparation method thereof, and belongs to the technical field of modified calcium carbonate preparation. The preparation process comprises the following steps: preparing porous vaterite-phase nano calcium carbonate; preparing high-strength filling porous vaterite phase nano calcium carbonate; and preparing high-strength modified calcium carbonate. According to the preparation method, 3-(methacryloyloxy) propyl trimethylsiloxane and poly (ethylene glycol) diacrylate are subjected to a polymerization reaction under the action of azodiisobutyronitrile, and then modified calcium carbonate is grafted, so that the compatibility and dispersity of the modified calcium carbonate and a polymer can be improved, and porous vaterite-phase nano calcium carbonate is prepared; the porous vaterite-phase nano calcium carbonate is subjected to filling modification, so that the strength of the porous vaterite-phase nano calcium carbonate can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of modified calcium carbonate preparation, and particularly relates to a high-strength modified calcium carbonate and a preparation method thereof. Background Art

[0002] Calcium carbonate, as a common inorganic compound, has a wide range of applications in many fields such as plastics, rubber, papermaking, coatings, and inks due to its wide sources, low price, non-toxic and harmless properties, etc. It can play roles such as filling, volume increasing, and cost reduction, and plays an important role in industrial production. However, ordinary calcium carbonate without modification treatment has many defects, which severely limit its application in the field of high-performance materials.

[0003] Firstly, the surface properties of calcium carbonate show strong hydrophilicity and poor compatibility with most organic polymer matrices (such as polyethylene, polypropylene, polyvinyl chloride, etc.). This leads to the agglomeration of calcium carbonate particles when filling calcium carbonate into organic polymers, and it is difficult to disperse evenly in the matrix. Uneven dispersion will not only reduce the mechanical properties of the composite material, such as tensile strength, bending strength, impact strength, etc., but also affect the processing performance of the material, for example, make the melt fluidity worse, increase the difficulty of extrusion or injection molding, and may even cause defects on the surface of the product, such as pitting, roughness, etc.

[0004] Secondly, the strength of calcium carbonate itself is relatively low. When the composite material is subjected to external forces, the calcium carbonate particles, as fillers, are difficult to effectively bear and transfer stress, but instead are prone to become stress concentration points, triggering the generation and expansion of cracks, thereby reducing the strength and durability of the entire composite material. This makes the method of simply relying on increasing the filling amount of calcium carbonate to reduce costs often counterproductive, because too high a filling amount will lead to a sharp decline in the comprehensive performance of the composite material.

[0005] Therefore, we propose a high-strength modified calcium carbonate and a preparation method thereof, which can not only significantly improve the compatibility and dispersibility of calcium carbonate with the organic matrix, but also effectively enhance the strength of calcium carbonate itself. Summary of the Invention

[0006] Aiming at the deficiencies of the existing technology, the purpose of the present invention is to provide a high-strength modified calcium carbonate and a preparation method thereof.

[0007] A high-strength modified calcium carbonate and a preparation method thereof include the following steps: S1: Preparation of porous vaterite phase nano calcium carbonate Add calcium carbide slag powder to NH4Ac solution, stir and mix, then filter by suction. Add the filtrate to a CO2 mineralization reactor, then add potassium hydroxide, glutamic acid and soluble starch, stir and mix, and finally introduce pure carbon dioxide gas. After the reaction, centrifuge, wash and dry to obtain porous vaterite-phase nano calcium carbonate; S2: Preparation of highly filled porous vaterite-phase nano calcium carbonate Prepare an oil-phase filler by mixing styrene, divinylbenzene and benzoyl peroxide. Then, use the oil-phase filler to preliminarily fill the porous vaterite-phase nano calcium carbonate. After that, carry out KH570 hydrolysis and condensation, and finally use the oil-phase filler to fill the remaining pores to obtain highly filled porous vaterite-phase nano calcium carbonate; S3: Preparation of highly modified calcium carbonate Use 3-(methacryloyloxy)propyltrimethylsiloxane and poly(ethylene glycol) diacrylate as raw materials to prepare a modifier, and then carry out graft modification on the highly filled porous vaterite-phase nano calcium carbonate to obtain highly modified calcium carbonate.

[0008] Furthermore, the preparation of the porous vaterite-phase nano calcium carbonate in step S1 specifically includes the following steps: S1.1: Grind calcium carbide slag into powder with a ball mill, pass it through a 100-120 mesh sieve, and store it sealed and away from light. Prepare NH4Ac solution, heat 15-18 parts by weight of NH4Ac solution to 40-45 °C, then add 200-230 parts by weight of calcium carbide slag powder, stir and mix for 20-30 min, and then filter by suction to obtain a filtrate and a filter residue; S1.2: Add the filtrate to a CO2 mineralization reactor, then add 5-8 parts by weight of potassium hydroxide and 1-2 parts by weight of glutamic acid, stir and mix, then add 3-5 parts by weight of soluble starch, put in a magnetic stirrer and start stirring, and at the same time measure the pH. When the pH is stable, introduce 500 ml / L of pure carbon dioxide gas. When the pH is stable for 5-6 min, obtain a suspension; S1.3: Place the suspension in a centrifuge, centrifuge to obtain a precipitate, wash the precipitate with ethanol 2-3 times, and then dry it in an oven at 70-80 °C to obtain porous vaterite-phase nano calcium carbonate.

[0009] Furthermore, the concentration of the NH4Ac solution in step S1.1 is 1 mol / L.

[0010] Furthermore, the preparation of the highly filled porous vaterite-phase nano calcium carbonate in step S2 specifically includes the following steps: S2.1: Mix styrene, divinylbenzene, and benzoyl peroxide, stir at room temperature for 10 - 12 h, then heat in a water bath at 60 - 62 °C for 1 - 2 h to obtain an oil-phase filler. Then, add 4 - 5 parts by weight of porous vaterite-phase nano calcium carbonate to 2 - 3 parts by weight of the oil-phase filler. After mixing, perform rotary evaporation under vacuum at 70 - 80 °C for 3 - 4 h, then perform suction filtration and dry at 70 - 80 °C for 2 - 3 h to obtain preliminarily filled calcium carbonate; S2.2: Place the preliminarily filled calcium carbonate in silane coupling agent KH570 so that the calcium carbonate is completely immersed, soak for 1 - 2 h. Then, mix 4 - 5 parts by weight of hydrochloric acid and 1 - 2 parts by weight of hydrofluoric acid to obtain a mixed acid. Mix the mixed acid with the soaked calcium carbonate and hydrolyze at 65 - 70 °C for 1 - 2 h. Then, wash with absolute ethanol 2 - 3 times and dry to obtain calcium carbonate after soaking and hydrolysis with silane coupling agent KH570; S2.3: Mix the calcium carbonate after soaking and hydrolysis with silane coupling agent KH570 with 1 - 2 parts by weight of the oil-phase filler, perform rotary evaporation under vacuum at 70 - 80 °C for 3 - 4 h, then perform suction filtration and dry at 70 - 80 °C for 2 - 3 h to obtain high-strength filled porous vaterite-phase nano calcium carbonate.

[0011] Further, in step 2.1, the mixing ratio of styrene, divinylbenzene, and benzoyl peroxide is 70 - 80:20 - 30:1 - 3.

[0012] Further, the preparation of high-strength modified calcium carbonate in step S3 specifically includes the following steps: S3.1: Add 40 - 50 parts by weight of poly(ethylene glycol) diacrylate to 60 - 70 parts by weight of acetone, stir and mix evenly to obtain a poly(ethylene glycol) diacrylate solution; S3.2: Dissolve 18 - 20 parts by weight of 3-(methacryloyloxy)propyltrimethylsiloxane and 0.3 - 0.5 parts by weight of azobisisobutyronitrile in 20 - 30 parts by weight of diethylene glycol dimethyl ether, then dropwise add the poly(ethylene glycol) diacrylate solution, heat to 60 - 65 °C, react for 20 - 24 h, and then wash and filter with cyclohexane to obtain a modifier; S3.3: Add 3 - 5 parts by weight of the modifier to 10 - 12 parts by weight of methanol, then add 5 - 8 parts by weight of high-strength filled porous vaterite-phase nano calcium carbonate, stir and mix, react at 60 - 62 °C for 20 - 30 min, then filter, and bake the precipitate at 100 - 120 °C for 1 - 2 h to obtain high-strength modified calcium carbonate.

[0013] A high-strength modified calcium carbonate, which is prepared by the preparation method of a high-strength modified calcium carbonate described in any one of the above.

[0014] Compared with the prior art, the present invention has at least the following beneficial effects: 1. The present invention realizes the coupling of 3-(methacryloyloxy)propyl trimethylsiloxane and poly(ethylene glycol) diacrylate by polymerization reaction under the action of azobisisobutyronitrile. Then, the siloxane group in 3-(methacryloyloxy)propyl trimethylsiloxane will chemically react with the hydroxyl group on the surface of calcium carbonate, thereby forming a chemical bond on the surface of calcium carbonate particles. The chemical bond makes the surface of modified calcium carbonate have organic functional groups, changes the original surface properties of calcium carbonate, and transforms it from hydrophilic to lipophilic, achieving the effect of graft modification. The polymer chain formed by poly(ethylene glycol) diacrylate during the reaction will be wrapped on the surface of calcium carbonate. When the modified calcium carbonate and the polymer During mixing, the poly (ethylene glycol) diacrylate chains wrapped on the surface of calcium carbonate can be entangled with the polymer matrix molecular chains, thereby improving the compatibility between calcium carbonate and the polymer, enabling better uniform dispersion therein, reducing agglomeration, and generating active groups during the coupling reaction. These active groups exist on the surface of the modified calcium carbonate. When in contact with the polymer, they can react with the corresponding active groups on the polymer molecular chains, thereby further improving the compatibility between calcium carbonate and the polymer. The wrapped polymer chains form a certain steric hindrance around the calcium carbonate particles, preventing direct contact and mutual attraction between the calcium carbonate particles, thereby reducing the possibility of particle agglomeration and facilitating the dispersion of calcium carbonate in the system, thereby improving the strength of the composite material.

[0015] 2. The present invention is based on the pore structure of porous vaterite-phase nano-calcium carbonate, utilizes capillary action to adsorb an oil-phase filler, and induces it to undergo free radical in-situ polymerization in the pores to form an organic cross-linked network. KH570 is then introduced to cause hydrolysis and condensation inside the calcium carbonate, and the remaining pores are filled with the oil-phase filler. The sol-gel reaction between KH570 and the oil-phase filler in the calcium carbonate pores generates a three-dimensional, dense organic-inorganic cross-linked network structure. The cross-linked network structure builds an internal scaffold inside the calcium carbonate, providing internal support within the pores of the calcium carbonate. When subjected to external force, the cross-linked network can bear part of the stress, preventing the calcium carbonate particles from being too close or squeezed together due to the force, resulting in structural damage. The cross-linked network can disperse the concentrated stress to a larger area, avoiding stress concentration in a local area, thereby reducing the possibility of calcium carbonate particle breakage or pore collapse, effectively improving the strength of the calcium carbonate, and then effectively improving the strength of the entire composite material.

[0016] 3. The present invention takes the NH4Ac solution and glutamic acid additive as the breakthrough point, adds soluble starch, and prepares porous vaterite-phase nano calcium carbonate. The NH4Ac solution has a high leaching rate of calcium ions as a leaching agent, and since the corresponding calcium salt calcium acetate has a high solubility in water, solid-liquid separation can be carried out by simple filtration. A new ammonium acetate leaching agent is selected to treat carbide slag, replacing the traditional ammonium chloride and hydrochloric acid leaching agents, solving the problem of pipeline corrosion and reducing the wastewater treatment cost.

[0017] 4. In the present invention, the carboxyl group of glutamic acid can interact with calcium ions in the solution and adsorb on the surface of calcium carbonate crystal nuclei, thereby changing the growth rate and growth direction of calcium carbonate crystals, inhibiting their transformation into the thermodynamically stable calcite phase, and thus facilitating the formation of vaterite-phase calcium carbonate. At the same time, the presence of glutamic acid can also increase the steric hindrance between calcium carbonate particles, prevent excessive aggregation of particles, and contribute to the formation of a porous structure. Starch molecules can self-assemble through hydrogen bonding and other interactions to form a three-dimensional network structure as a template for calcium carbonate crystallization. When calcium carbonate precipitates in the solution, it will grow on the template of starch molecules, being restricted and guided by the template, thereby forming porous vaterite-phase nano calcium carbonate. The porous vaterite-phase nano calcium carbonate has an increased specific surface area, can provide more active sites, is conducive to subsequent graft modification, and due to the presence of the porous structure, the aggregation phenomenon between vaterite-phase nano calcium carbonate particles is effectively inhibited, and the dispersibility in the polymer matrix is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The drawings incorporated herein and constituting a part of the specification illustrate embodiments of the present invention and, together with the specification, are further used to explain the principles of the present invention and enable those skilled in the relevant art to implement and use the present invention.

[0019] Figure 1 It is a flowchart of a preparation method of a high-strength modified calcium carbonate adopted in an embodiment of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0020] The following describes in detail a preparation method of a high-strength modified calcium carbonate provided by the present invention in conjunction with the drawings and specific embodiments. At the same time, it is hereby explained that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art can also adopt other alternative methods for some well-known technologies; moreover, the drawing part is only for more specifically describing the embodiments and is not intended to specifically limit the present invention.

[0021] Example 1 A preparation method of a high-strength modified calcium carbonate, as Figure 1 shown, includes the following steps: S1: Preparation of Porous Vaterite Phase Nano Calcium Carbonate S1.1: Grind carbide slag into powder with a ball mill, sieve it through a 100-mesh sieve, and store it sealed and backlit. Prepare a 1 mol / L NH4Ac solution, heat 15 parts by weight of the NH4Ac solution to 40 °C, then add 200 parts by weight of carbide slag powder, stir and mix for 20 min, then filter by suction to obtain a filtrate and a filter residue; S1.2: Add the filtrate to a CO2 mineralization reaction kettle, then add 5 parts by weight of potassium hydroxide and 1 part by weight of glutamic acid, stir and mix, then add 3 parts by weight of soluble starch, put in a magnetic stirrer and start stirring, and measure the pH at the same time. When the pH is stable, introduce 500 ml / L of pure carbon dioxide gas. When the pH is stable for 5 min, a suspension is obtained; S1.3: Place the suspension in a centrifuge, centrifuge to obtain a precipitate, wash the precipitate twice with ethanol, and then dry it in an oven at 70 °C to obtain porous vaterite phase nano calcium carbonate; S2: Preparation of High-Strength Filled Porous Vaterite Phase Nano Calcium Carbonate S2.1: Mix 70 parts by weight of styrene, 20 parts by weight of divinylbenzene, and 1 part by weight of benzoyl peroxide, stir at room temperature for 10 h, then heat in a water bath at 60 °C for 1 h to obtain an oil-phase filler. Then add 4 parts by weight of porous vaterite phase nano calcium carbonate to 2 parts by weight of the oil-phase filler, mix, rotary evaporate under vacuum at 70 °C for 3 h, then filter by suction, and dry at 70 °C for 2 h to obtain preliminarily filled calcium carbonate; S2.2: Place the preliminarily filled calcium carbonate in the silane coupling agent KH570 so that the calcium carbonate is completely immersed, soak for 1 h. Then mix 4 parts by weight of hydrochloric acid and 1 part by weight of hydrofluoric acid to obtain a mixed acid. Mix the mixed acid with the soaked calcium carbonate and hydrolyze at 65 °C for 1 h, then wash twice with absolute ethanol and dry again to obtain calcium carbonate after being soaked and hydrolyzed by the silane coupling agent KH570; S2.3: Mix the calcium carbonate after being soaked and hydrolyzed by the silane coupling agent KH570 with 1 part by weight of the oil-phase filler, rotary evaporate under vacuum at 70 °C for 3 h, then filter by suction, and dry at 70 °C for 2 h to obtain high-strength filled porous vaterite phase nano calcium carbonate; S3: Preparation of High-Strength Modified Calcium Carbonate S3.1: Add 40 parts by weight of poly(ethylene glycol) diacrylate to 60 parts by weight of acetone, stir and mix evenly to obtain a poly(ethylene glycol) diacrylate solution; S3.2: Dissolve 18 parts by weight of 3-(methacryloyloxy)propyltrimethylsiloxane and 0.3 parts by weight of azobisisobutyronitrile in 20 parts by weight of diethylene glycol dimethyl ether. Then, dropwise add a poly(ethylene glycol) diacrylate solution, heat to 60 °C, and react for 20 h. After that, wash with cyclohexane and filter to obtain a modifier. S3.3: Add 3 parts by weight of the modifier to 10 parts by weight of methanol, then add 5 parts by weight of high-strength filled porous vaterite-phase nano calcium carbonate. After stirring and mixing, react at 60 °C for 20 min, then filter. Bake the precipitate at 100 °C for 1 h to obtain high-strength modified calcium carbonate.

[0022] Example 2 A preparation method of high-strength modified calcium carbonate, as Figure 1 shown, includes the following steps: S1: Preparation of porous vaterite-phase nano calcium carbonate S1.1: Grind carbide slag into powder with a ball mill, pass through a 120-mesh sieve, and store it sealed and backlit. Prepare a 1 mol / L NH4Ac solution, heat 15 parts by weight of the NH4Ac solution to 45 °C, then add 200 parts by weight of carbide slag powder, stir and mix for 30 min, then filter by suction to obtain a filtrate and a filter residue. S1.2: Add the filtrate to a CO2 mineralization reaction kettle, then add 5 parts by weight of potassium hydroxide and 1 part by weight of glutamic acid. After stirring and mixing, add 3 parts by weight of soluble starch, put in a magnetic stirrer and start stirring, and measure the pH at the same time. When the pH is stable, introduce pure carbon dioxide gas at 500 ml / L. When the pH is stable for 6 min, obtain a suspension. S1.3: Place the suspension in a centrifuge, centrifuge to obtain a precipitate, wash the precipitate with ethanol 3 times, then put it in an 80 °C oven to dry to obtain porous vaterite-phase nano calcium carbonate. S2: Preparation of high-strength filled porous vaterite-phase nano calcium carbonate S2.1: Mix 70 parts by weight of styrene, 20 parts by weight of divinylbenzene, and 1 part by weight of benzoyl peroxide, stir at room temperature for 12 h, then heat in a 62 °C water bath for 2 h to obtain an oil-phase filler. Then, add 4 parts by weight of porous vaterite-phase nano calcium carbonate to 2 parts by weight of the oil-phase filler. After mixing, perform rotary evaporation under vacuum at 80 °C for 4 h, then filter by suction and dry at 80 °C for 3 h to obtain preliminarily filled calcium carbonate. S2.2: Place the preliminarily filled calcium carbonate into the silane coupling agent KH570 so that the calcium carbonate is completely immersed, soak for 2 h. Then mix 4 parts by weight of hydrochloric acid with 1 part by weight of hydrofluoric acid to obtain a mixed acid. Mix the mixed acid with the soaked calcium carbonate and hydrolyze at 70 °C for 2 h. Then wash with absolute ethanol 3 times and dry to obtain calcium carbonate after being soaked and hydrolyzed by the silane coupling agent KH570; S2.3: Then mix the calcium carbonate after being soaked and hydrolyzed by the silane coupling agent KH570 with 1 part by weight of an oil-phase filler, perform rotary evaporation under vacuum at 80 °C for 4 h, then carry out suction filtration and dry at 80 °C for 3 h to obtain high-strength filled vaterite-phase nano calcium carbonate; S3: Preparation of high-strength modified calcium carbonate S3.1: Add 40 parts by weight of poly(ethylene glycol) diacrylate to 60 parts by weight of acetone, stir and mix evenly to obtain a poly(ethylene glycol) diacrylate solution; S3.2: Dissolve 18 parts by weight of 3-(methacryloyloxy)propyltrimethylsiloxane and 0.3 part by weight of azobisisobutyronitrile in 20 parts by weight of diethylene glycol dimethyl ether, then dropwise add the poly(ethylene glycol) diacrylate solution, heat to 65 °C, react for 24 h, and then wash and filter with cyclohexane to obtain a modifier; S3.3: Add 3 parts by weight of the modifier to 10 parts by weight of methanol, then add 5 parts by weight of high-strength filled vaterite-phase nano calcium carbonate, stir and mix, react at 62 °C for 30 min, then filter, and bake the precipitate at 120 °C for 2 h to obtain high-strength modified calcium carbonate.

[0023] Example 3 A preparation method of high-strength modified calcium carbonate, as Figure 1 shown, includes the following steps: S1: Preparation of vaterite-phase nano calcium carbonate S1.1: Grind carbide slag into powder with a ball mill, pass through a 100-mesh sieve, and store it sealed in the backlight. Prepare a 1 mol / L NH4Ac solution, heat 18 parts by weight of the NH4Ac solution to 40 °C, then add 230 parts by weight of carbide slag powder, stir and mix for 20 min, then carry out suction filtration to obtain a filtrate and a filter residue; S1.2: Add the filtrate to a CO2 mineralization reaction kettle, then add 8 parts by weight of potassium hydroxide and 2 parts by weight of glutamic acid, stir and mix, then add 5 parts by weight of soluble starch, put in a magnetic stirrer and start stirring, and measure the pH at the same time. When the pH is stable, introduce pure carbon dioxide gas at 500 ml / L. When the pH is stable for 5 min, obtain a suspension; S1.3: Place the suspension in a centrifuge, centrifuge to obtain a precipitate, wash the precipitate twice with ethanol, and then dry it in an oven at 70 °C to obtain porous vaterite-phase nano calcium carbonate; S2: Preparation of highly filled porous vaterite-phase nano calcium carbonate S2.1: Mix 80 parts by weight of styrene, 30 parts by weight of divinylbenzene, and 3 parts by weight of benzoyl peroxide, stir at room temperature for 10 h, then heat in a water bath at 60 °C for 1 h to obtain an oil-phase filler. Then, add 5 parts by weight of porous vaterite-phase nano calcium carbonate to 3 parts by weight of the oil-phase filler, mix, rotary evaporate under vacuum at 70 °C for 3 h, then perform suction filtration, and dry at 70 °C for 2 h to obtain preliminarily filled calcium carbonate; S2.2: Place the preliminarily filled calcium carbonate in silane coupling agent KH570 so that the calcium carbonate is completely immersed, soak for 1 h. Then, mix 5 parts by weight of hydrochloric acid and 2 parts by weight of hydrofluoric acid to obtain a mixed acid. Mix the mixed acid with the soaked calcium carbonate and hydrolyze at 65 °C for 1 h. Then, wash twice with absolute ethanol and dry to obtain calcium carbonate after being soaked and hydrolyzed with silane coupling agent KH570; S2.3: Mix the calcium carbonate after being soaked and hydrolyzed with silane coupling agent KH570 with 2 parts by weight of the oil-phase filler, rotary evaporate under vacuum at 70 °C for 3 h, then perform suction filtration, and dry at 70 °C for 2 h to obtain highly filled porous vaterite-phase nano calcium carbonate; S3: Preparation of highly modified calcium carbonate S3.1: Add 50 parts by weight of poly(ethylene glycol) diacrylate to 70 parts by weight of acetone, stir and mix evenly to obtain a poly(ethylene glycol) diacrylate solution; S3.2: Dissolve 20 parts by weight of 3-(methacryloyloxy)propyltrimethylsiloxane and 0.5 parts by weight of azobisisobutyronitrile in 30 parts by weight of diethylene glycol dimethyl ether, then dropwise add the poly(ethylene glycol) diacrylate solution, heat to 60 °C, react for 20 h, and then wash and filter with cyclohexane to obtain a modifier; S3.3: Add 5 parts by weight of the modifier to 12 parts by weight of methanol, then add 8 parts by weight of highly filled porous vaterite-phase nano calcium carbonate, stir and mix, react at 60 °C for 20 min, then filter, and bake the precipitate at 100 °C for 1 h to obtain highly modified calcium carbonate.

[0024] Comparative Example 1 Compared with Example 1, the difference in Comparative Example 1 is that Comparative Example 1 prepares highly filled porous vaterite-phase nano calcium carbonate, which is highly modified calcium carbonate, by removing step S3 and keeping the other steps unchanged, denoted as Comparative Example 1.

[0025] Comparative Example 2 Compared with Example 1, the difference in Comparative Example 2 is that in Comparative Example 2, steps S2.2 - S2.3 are removed, and the highly filled porous vaterite phase nano calcium carbonate in step S3.3 is replaced with calcium carbonate after preliminary filling in an equal weight portion, and the remaining steps remain unchanged to prepare highly modified calcium carbonate, denoted as Comparative Example 2.

[0026] Comparative Example 3 Compared with Example 1, the difference in Comparative Example 3 is that in Comparative Example 3, step S2 is removed, and the highly filled porous vaterite phase nano calcium carbonate in step S3.3 is replaced with porous vaterite phase nano calcium carbonate in an equal weight portion, and the remaining steps remain unchanged to prepare highly modified calcium carbonate, denoted as Comparative Example 3.

[0027] Comparative Example 4 Compared with Example 1, the difference in Comparative Example 4 is that in Comparative Example 4, step S1 is removed, and the porous vaterite phase nano calcium carbonate in step S2.1 is replaced with nano calcium carbonate in an equal weight portion, and the remaining steps remain unchanged to prepare highly modified calcium carbonate, denoted as Comparative Example 4.

[0028] The highly modified calcium carbonate prepared in Examples 1 - 3 and Comparative Examples 1 - 4 was mixed with polypropylene in a weight ratio of 3:20, added to a mixer and stirred. The rotation speed was controlled at 300 r / min, the stirring temperature was 70 °C, and the stirring time was 2 minutes. Then it was extruded and granulated by a screw extruder, the extrusion temperature was 180 °C, and it was cooled and formed in cold water at 10 °C to obtain a highly modified calcium carbonate filled polypropylene composite material, and its properties were measured, and the performance test results are shown in Table 1.

[0029] Table 1. Performance measurement results of Examples 1 - 3 and Comparative Examples 1 - 4

[0030] It can be seen from the data in Table 1 that the data of Comparative Example 1 are significantly lower than those of the Examples, indicating that graft modification of calcium carbonate by coupling 3 - (methacryloyloxy)propyltrimethylsiloxane and poly(ethylene glycol) diacrylate effectively improves the strength of the composite material, indicating that graft modification can improve the dispersibility of calcium carbonate and its compatibility with polypropylene. It can be seen from the data of Comparative Examples 2 - 3 that the strength also decreases significantly, indicating that filling and modifying the porous vaterite phase nano calcium carbonate effectively improves the strength of calcium carbonate, thereby improving the strength of the composite material, and compared with single - time filling of the oil - phase filler, introducing the oil - phase filler again after the hydrolysis and condensation of KH570 has a better effect on improving the strength of calcium carbonate. It can be seen from the data of Comparative Example 4 that using the porous vaterite phase nano calcium carbonate as the raw material for filling and modification has a better effect on improving the strength compared with nano calcium carbonate, indicating that the porous vaterite phase nano calcium carbonate prepared by the present invention is more conducive to filling and graft modification, thereby improving the strength.

[0031] Comparative Example 5 Compared with Example 1, the difference in Comparative Example 5 is that the NH4Ac solution in step S1.1 is replaced with ammonium chloride of the same concentration and equal weight parts, and the remaining steps remain unchanged to prepare high-strength modified calcium carbonate, denoted as Comparative Example 5.

[0032] Comparative Example 6 Compared with Example 1, the difference in Comparative Example 6 is that the NH4Ac solution in step S1.1 is replaced with ammonium citrate of the same concentration and equal weight parts, and the remaining steps remain unchanged to prepare high-strength modified calcium carbonate, denoted as Comparative Example 6.

[0033] Determine the calcium ion leaching effect: Perform chemical component analysis on the raw materials using XRF analysis. The instrument selected is an X-ray fluorescence spectrometer with the model RIGAKU-ZSX-Priums from the Dutch manufacturer PANalytical-Axios. The test of this equipment adopts the oxide + elemental mode.

[0034] Test element range: 11Na - 92U; The calculation formula is as follows: ω1 = m Ca / m0 × 100%; ω2 = (m Ca -∆m) / (m0 - ∆m); where m Ca is the mass of calcium element in carbide slag, m0 is the mass of carbide slag, and ∆m is the mass of calcium element in porous vaterite phase nano calcium carbonate; The leaching rate is θ = (ω1 - ω2) / (1 - ω2) × 100%, where ω1 is the mass fraction of calcium element in carbide slag; ω2 is the mass fraction of calcium element in the filter residue; Refer to Table 2 for the determination results of the leaching rate.

[0035] Table 2. Determination Results of Leaching Rates of Example 1 and Comparative Examples 5 - 6

[0036] It can be seen from the data in Table 2 that there is not much difference between Example 1 and Comparative Example 5, but it is significantly higher than Comparative Example 6. From the data of Comparative Example 6, it can be seen that the leaching rate of ammonium citrate for calcium ions is small. Since the calcium ion concentration is too small to meet the requirements of subsequent mineralization reactions, it is necessary to add an evaporation and concentration step for concentration, which not only increases the equipment complexity but also increases the cost. From the data of Comparative Example 5 and Example 1, it can be seen that the present invention uses NH4Ac as the leaching agent, and there is not much difference in the leaching effect compared with the ammonium chloride leaching agent. The ammonium chloride leaching agent has a high leaching rate for calcium ions in carbide slag, but the long-term corrosion of metal pipes by chloride ions will reduce the service life of the equipment, thus increasing the equipment operation cost of the entire leaching process. At the same time, the waste liquid also contains a large amount of chloride ions, seriously polluting the environment. However, NH4Ac as the leaching agent has a high leaching rate for calcium ions, and the waste liquid does not contain chloride ions, which can solve the problems of pipeline corrosion and reduce the waste water treatment cost.

[0037] The above embodiments are only illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Any person familiar with this technology can modify or change the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by those with ordinary knowledge in the technical field without departing from the spirit and technical ideas disclosed by the present invention should still be covered by the claims of the present invention.

Claims

1. A preparation method of high-strength modified calcium carbonate, characterized in that, It includes the following steps: S1: Preparation of porous vaterite-phase nano calcium carbonate Add calcium carbide slag powder to NH4Ac solution, stir and mix, then filter by suction. Add the filtrate into a CO2 mineralization reactor, then add potassium hydroxide, glutamic acid and soluble starch, stir and mix, and finally introduce pure carbon dioxide gas. After the reaction, centrifuge, wash and dry to obtain porous vaterite-phase nano calcium carbonate; S2: Preparation of highly filled porous vaterite-phase nano calcium carbonate Prepare an oil-phase filler by mixing styrene, divinylbenzene and benzoyl peroxide. Then, use the oil-phase filler to preliminarily fill the porous vaterite-phase nano calcium carbonate. After that, carry out KH570 hydrolysis and condensation. Finally, use the oil-phase filler to fill the remaining pores to obtain highly filled porous vaterite-phase nano calcium carbonate; S3: Preparation of highly modified calcium carbonate Use 3-(isobutenyloxy)propyltrimethylsiloxane and poly(ethylene glycol) diacrylate as raw materials to prepare a modifier, and then carry out graft modification on the highly filled porous vaterite-phase nano calcium carbonate to obtain highly modified calcium carbonate.

2. The preparation method of a high-strength modified calcium carbonate according to claim 1, characterized in that, The preparation of porous vaterite-phase nano calcium carbonate in step S1 specifically includes the following steps: S1.1: Grind calcium carbide slag into powder with a ball mill, pass it through a 100-120 mesh sieve, and store it sealed and away from light. Prepare NH4Ac solution, heat 15-18 parts by weight of NH4Ac solution to 40-45 °C, then add 200-230 parts by weight of calcium carbide slag powder, stir and mix for 20-30 min, and then filter by suction to obtain a filtrate and a filter residue; S1.2: Add the filtrate into a CO2 mineralization reactor, then add 5-8 parts by weight of potassium hydroxide and 1-2 parts by weight of glutamic acid, stir and mix, then add 3-5 parts by weight of soluble starch, put in a magnetic stirrer and start stirring, and measure the pH at the same time. When the pH is stable, introduce 500 ml / L pure carbon dioxide gas. When the pH is stable for 5-6 min, obtain a suspension; S1.3: Place the suspension in a centrifuge, centrifuge to obtain a precipitate, wash the precipitate with ethanol 2-3 times, and then dry it in an oven at 70-80 °C to obtain porous vaterite-phase nano calcium carbonate.

3. The preparation method of a high-strength modified calcium carbonate according to claim 2, characterized in that, The concentration of the NH4Ac solution in step S1.1 is 1 mol / L.

4. The preparation method of a high-strength modified calcium carbonate according to claim 1, characterized in that, The preparation of highly filled porous vaterite-phase nano calcium carbonate in step S2 specifically includes the following steps: S2.1: Mix styrene, divinylbenzene and benzoyl peroxide and stir at room temperature for 10-12 h, then heat in a water bath at 60-62 °C for 1-2 h to obtain an oil-phase filler. Then, add 4-5 parts by weight of porous vaterite-phase nano calcium carbonate to 2-3 parts by weight of the oil-phase filler. After mixing, rotary evaporate under vacuum at 70-80 °C for 3-4 h, then filter by suction, and dry at 70-80 °C for 2-3 h to obtain preliminarily filled calcium carbonate; S2.2: Place the preliminarily filled calcium carbonate into the silane coupling agent KH570 so that the calcium carbonate is completely immersed, soak for 1 - 2 h. Then mix 4 - 5 parts by weight of hydrochloric acid with 1 - 2 parts by weight of hydrofluoric acid to obtain a mixed acid. Mix the mixed acid with the soaked calcium carbonate and hydrolyze at 65 - 70 °C for 1 - 2 h. Then wash with absolute ethanol 2 - 3 times and dry to obtain calcium carbonate after being soaked and hydrolyzed by the silane coupling agent KH570; S2.3: Then mix the calcium carbonate after being soaked and hydrolyzed by the silane coupling agent KH570 with 1 - 2 parts by weight of an oil - phase filler, carry out rotary evaporation under vacuum at 70 - 80 °C for 3 - 4 h, then carry out suction filtration and dry at 70 - 80 °C for 2 - 3 h to obtain high - strength filled porous vaterite - phase nano calcium carbonate.

5. The preparation method of a high-strength modified calcium carbonate according to claim 4, characterized in that, In step 2.1, the mixing ratio of styrene, divinylbenzene, and benzoyl peroxide is 70 - 80:20 - 30:1 - 3.

6. The preparation method of a high-strength modified calcium carbonate according to claim 1, characterized in that, Step S3: Preparation of high - strength modified calcium carbonate, which specifically includes the following steps: S3.1: Add 40 - 50 parts by weight of poly(ethylene glycol) diacrylate to 60 - 70 parts by weight of acetone, stir and mix evenly to obtain a poly(ethylene glycol) diacrylate solution; S3.2: Dissolve 18 - 20 parts by weight of 3 - (methacryloyloxy)propyltrimethylsiloxane and 0.3 - 0.5 parts by weight of azobisisobutyronitrile in 20 - 30 parts by weight of diethylene glycol dimethyl ether. Then dropwise add the poly(ethylene glycol) diacrylate solution, heat to 60 - 65 °C, react for 20 - 24 h, and then wash and filter with cyclohexane to obtain a modifier; S3.3: Add 3 - 5 parts by weight of the modifier to 10 - 12 parts by weight of methanol, then add 5 - 8 parts by weight of high - strength filled porous vaterite - phase nano calcium carbonate, stir and mix, react at 60 - 62 °C for 20 - 30 min, then filter, and bake the precipitate at 100 - 120 °C for 1 - 2 h to obtain high - strength modified calcium carbonate.

7. A high-strength modified calcium carbonate, characterized in that, It is prepared by the preparation method of a high - strength modified calcium carbonate described in any one of the above claims 1 - 6.

Citation Information

Cited By

  • Preparation method and application of nano calcium carbonate for PU elastomer

    CN121085307A